Successful expectant management of tubal heterotopic pregnancy - Baxi, Asha (Medknow Publications, 2010)
Expectant management for tubal heterotopic pregnancy could be considered as a successful option in a symptom-free patient where the ectopic embryo has a limited craniocaudal length with no cardiac activity. We report the obstetric outcome after expectant management for a right tubal heterotopic pregnancy. Heterotopic pregnancy was first recognized at 6 weeks gestation in a 32-year-old salpingectomized woman with an 8-year history of subfertility who conceived after in utero transfer of three embryos obtained by in vitro fertilization. Expectant management and close ultrasonographic and clinical monitoring were done. The intrauterine pregnancy proceeded unremarkably. A cesarean section was performed for breech presentation, and it allowed the delivery of a healthy 2260-g male infant. The examination of the adnexa showed a pre-rupture of the right fallopian tube.